Improving the representation of modal choice into bottom-up optimization energy system models – The MoCho-TIMES model. (15th February 2018) - Tattini, Jacopo; Ramea, Kalai; Gargiulo, Maurizio; Yang, Christopher; Mulholland, Eamonn; Yeh, Sonia; Karlsson, Kenneth
Highlights: Novel methodology for representing modal choice into energy system models is presented. Heterogeneity of transport users is introduced to differentiate modal perceptions. Preferences accounted through monetization of intangible costs. Value of time and level of service variables are accounted by the model. Approach paves the way to new policy analyses involving novel attributes. Abstract: This study presents MoCho-TIMES, an original methodology for incorporating modal choice into energy-economy-environment-engineering (E4) system models. MoCho-TIMES addresses the scarce ability of E4 models to realistically depict behaviour in transport and allows for modal shift towards transit and non-motorized modes as a new dimension for decarbonising the transportation sector. The novel methodology determines endogenous modal shares by incorporating variables related to the level-of-service (LoS) of modes and consumers' modal perception within the E4 modeling framework. Heterogeneity of transport users is introduced to differentiate modal perception and preferences across different consumer groups, while modal preferences are quantified via monetization of intangible costs. A support transport simulation model consistent with the geographical scope of the E4 model provides the data and mathematical expressions required to develop the approach. This study develops MoCho-TIMES in the standalone transportation sector of TIMES-DK, the integrated energy system model for Denmark. The model is tested for the Business as Usual scenario and for four alternative scenarios that imply diverse assumptions for the new attributes introduced. The results show that different assumptions for the new attributes affect modal shares and CO2 emissions. MoCho-TIMES inaugurates the possibility to perform innovative policy analyses involving new parameters to the E4 modeling framework. The results find that authority's commitment to sustainability is crucial for a paradigmatic change in the transportation sector.